อนาคตภาพการบริหารจัดการองค์การพยาบาล โรงพยาบาลมหาวิทยาลัยในกำกับของรัฐ ช่วงพุทธศักราช 2565-2569 - นครินทร์ กมณีย์ (สมาคมพยาบาลทหารบก, 2022)
The purpose of this research was to study a scenario of nursing organization management, autonomous university hospitals during B.E. 2022-2026. The Ethnographic Delphi Future Research (EDFR) was applied. The subject were 20 experts including two chief administrator from Ministry of Public Health, eight nursing administrators of autonomous university hospital, four nurse executive and six administrative lecturers from autonomous university hospital. The EDFR consisted of three steps : In step one, the experts were asked to describe about nursing organizational management. In step two, the data were analyzed by using content analysis for developing the rating scale questionnaire. All items in the questionnaire were ranked by the level probability of each scenario by organization management expertist. In step three, the data from the questionnaire were analyzed by median and interquatile range and then a new version of questionnaire was developed. The data were analyzed again by using median and interquatile range to summarize the nursing organizational management. The results showed that the future of nursing organization management autonomous university hospitals during B.E. 2022-2026 consists of 8 aspects of the future 1. Organizational strategy 2. Organizational structure 3. System 4. Nursing resource management 5. Management 6. Service 7. Information technology and 8. Education